Physiological Effects of Single Shocks on the Hand-Arm System—A Randomized Experiment - Elke Ochsmann; Alexandra Corominas; Uwe Kaulbars; Hans Lindell; Benjamin Ernst (Proceedings, 2023)
Physiological health effects (vibration perception thresholds and infrared skin temperature) of single-impact exposures and vibration exposures have been evaluated. In this experiment, a total of 52 healthy male participants were randomly exposed to single shocks of different frequencies (1 s−1, 4 s−1, and 20 s−1) and to random signal vibration exposures (4 × 5 min exposure duration). We observed frequency-dependent and eventually dose-dependent physiological effects. No exposure parameter systematically correlated to any of the examined physiological outcomes. This could hint at different pathways for physiological effects.